Skin Manifestation of Crohn's Disease - Rahman, Moch. Aulia; Islamy, Muhammad Habiel; Harliza, Baiq Fanindya; Iqlima, Aisya Yafis; Lukman, Dian Azizah; Azmi, Naurah Arika; Fariztia, Alifia Intan; Humam, Anang Muh. Naufal; Salsabila, Maida Sania; Akbar, Nugraha Malik; Alaydrus, M. Mukaddam (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Skin Manifestation of Internal Disease is a condition that refers to changes or abnormalities in the skin that are related to or caused by systemic diseases or disorders of other internal organs of the body. Sweet's Syndrome as one of the skin manifestations that can occur in patients with Crohn's Disease. The purpose of this article is to determine the definition, etiology, epidemiology, pathophysiology, clinical manifestations, epidemiology and management of skin manifestations of Crohn's disease. The method used is a literature review of articles related to Skin Manifestation of Crohn's disease, which processes information and data from various related articles to obtain conclusions. Articles used related to this study were obtained through searches in databases such as PubMed, Google Scholar, and Sciencedirect. The publication year limit used in this article is at least 10 years. Sweet's Syndrome or known as Acute Febrile Neutrophilic Dermatosis (AFND) is a prototype of neutrophilic dermatosis disease characterized by acute onset neutrophilic dermal lesions, leukocytosis, and pyrexia. Based on its etiology, sweet syndrome is grouped into 3 subtypes: Classic Sweet's Syndrome (Idiopathic Sweet's Syndrome), Drug Induced Sweet's Syndrome, Malignancy-Associated Sweet's Syndrome. Therefore, it is important for clinicians to recognize Sweet's syndrome as one of the skin manifestations in CD patients so that appropriate treatment can be given.